2017
DOI: 10.1093/mnras/stx856
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of eccentricity and inclination of hot protoplanets embedded in radiative discs

Abstract: We study the evolution of the eccentricity and inclination of protoplanetary embryos and low-mass protoplanets (from a fraction of an Earth mass to a few Earth masses) embedded in a protoplanetary disc, by means of three dimensional hydrodynamics calculations with radiative transfer in the diffusion limit. When the protoplanets radiate in the surrounding disc the energy released by the accretion of solids, their eccentricity and inclination experience a growth toward values which depend on the luminosity to ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 31 publications
9
70
0
Order By: Relevance
“…This implies that the eccentricity and inclination damping on a non-luminous embryo is completely dominated by thermal effects, which are nearly one order of magnitude more important than those arising from wave launching. This strong damping is in agreement with the findings of Eklund & Masset (2017) who found that the eccentricity and inclination of a non-luminous low-mass planet embedded in a radiative disc was indeed much stronger than that expected from Tanaka & Ward's formulae. When > 1, i.e.…”
Section: Time Evolution Of Eccentricity and Inclinationsupporting
confidence: 92%
See 3 more Smart Citations
“…This implies that the eccentricity and inclination damping on a non-luminous embryo is completely dominated by thermal effects, which are nearly one order of magnitude more important than those arising from wave launching. This strong damping is in agreement with the findings of Eklund & Masset (2017) who found that the eccentricity and inclination of a non-luminous low-mass planet embedded in a radiative disc was indeed much stronger than that expected from Tanaka & Ward's formulae. When > 1, i.e.…”
Section: Time Evolution Of Eccentricity and Inclinationsupporting
confidence: 92%
“…• The numerical experiments of Eklund & Masset (2017), which were performed prior to the existence of this work and were therefore not aimed at checking analytical predictions with a high accuracy, do show that planets are subjected to effects similar to those described here (i.e. excitation of eccentricity and inclination at large luminosity, as opposed to a strong damping of these quantities when they are nonluminous).…”
Section: Relation To Horseshoe Dynamicsmentioning
confidence: 95%
See 2 more Smart Citations
“…There are a number of shortcomings in our analysis. While we take into account the effects of the planet's luminosity on the time evolution of its semi-major axis, we neglect its impact on the eccentricity and inclination, which is potentially quite strong (Eklund & Masset 2017;Chrenko et al 2017). Sizeable eccentricities and inclinations may significantly alter the migration paths of planetary embryos, and may also affect the accretion rate on the embryos (Chrenko et al 2017) and the rate of collisions between embryos.…”
Section: Summary and Discussionmentioning
confidence: 99%